Targeted development :industrialized country strategy in a globalizing world - Bermeo, Sarah Blodgett (OUP, 2018)
In a globalizing world, the world's wealthiest nations have found it increasingly difficult to insulate themselves from the residual impacts associated with underdevelopment abroad. Many of the ills associated with, and exacerbated by, underdevelopment-illegal migration, political instability,refugee flows, illicit trafficking, disease outbreaks, terrorism, pollution, and others-cannot be confined within national borders. In Targeted Development, Sarah Bermeo shows how wealthy states have responded to this problem by transforming the very nature of development policy. Instead of fundingdevelopment projects that enhance human well-being in the most general sense, they now pursue a "targeted" strategy: advocating development abroad when and where it serves their own interests. In an era in which the ideology of "globalism" is in decline, targeted development represents a fundamentalshift toward a realpolitik approach toward foreign aid. Devising development plans that ultimately protect and benefit industrialized donor states now drives the agenda, while crafting effective solutions for deep-seated problems in the neediest nations is increasingly an afterthought.